Efficient CAD Model to Analysis of High Tc Superconducting Circular Microstrip Antenna on Anisotropic Substrates. Advanced Electromagnetics, e-ISSN 2119-0275 - Sami, Bedra; Randa, Bedra; Siham, Benkouda; Tarek, Fortaki (2017)
In this paper, an electromagnetic approach based on cavity model in conjunction with electromagnetic knowledge was developed. The cavity model combined with London’s equations and the Gorter-Casimir two-fluid model has been improved to investigate the resonant characteristics of high Tc superconducting circular microstrip patch in the case where the patch is printed on uniaxially anisotropic substrate materials.  Merits of our extended model include low computational cost and mathematical simplify. The numerical simulation of this modeling shows excellent agreement with experimental results available in the literature. Finally, numerical results for the dielectric anisotropic substrates effects on the operating frequencies for the case of superconducting circular patch are also presented.